533TiPCANOPY-2: A phase III, placebo-controlled study of canakinumab with or without docetaxel in patients (pts) with NSCLC previously treated with PD-(L)1 inhibitors and platinum-based chemotherapy (Ctx). (24th November 2019) - Lim, D; Goto, Y; Cho, B C; Kaneda, H; Kang, J-H; Kim, S-W; Chiu, C-H; Yang, J C-H; Su, W-C; Obyrne, K; Papadimitrakopoulou, V; Reck, M; et al.
Abstract: Background: Pembrolizumab, a PD-1 inhibitor combined with platinum-based Ctx is standard therapy for eligible pts without a targetable mutation, stage IIIB/IV NSCLC. Currently, there is no data to guide treatment following progression on sequential/concomitant use of platinum-based Ctx and PD-1 inhibitors. Activation of inflammation and elevated baseline c-reactive protein (CRP) levels are associated with a lower response to immunotherapies. Canakinumab is a high-affinity anti-IL-1β monoclonal antibody that showed a significant reduction in the incidence of fatal and nonfatal lung cancer in myocardial infarction pts with increased CRP levels (CANTOS study). Trial design: CANOPY-2 (NCT03626545) is a multicenter, phase 3 study evaluating the safety and efficacy of docetaxel ± canakinumab in pts with squamous/non-squamous, stage IIIB-IV NSCLC. This study includes a safety run-in part (part 1 – open-label) to confirm recommended phase 3 regimen (RP3R) to be used in the randomized phase 3 part (part 2 – double-blind, placebo-controlled). Key inclusion criteria: adult pts pretreated with one prior platinum-based Ctx and one prior PD-(L)1 inhibitor therapy for locally advanced or metastatic disease, either together/sequentially and then progressed; ECOG PS 0-1. In part 1, ∼9 pts will be enrolled to have at least 6 evaluable pts and ∼226 pts will be randomized (1:1, stratified by the number of prior lines of therapy and histology) in part 2 to docetaxel ± canakinumab. Primary objectives: to confirm RP3R of canakinumab + docetaxel, as determined by the incidence of dose-limiting toxicity in the first 42 days of administration (part 1) and overall survival (part 2). Secondary objectives: overall response rate, disease control rate, duration of response, time to response, progression-free survival by investigator (RECIST v1.1), safety, PK, immunogenicity of canakinumab, and patient-reported outcomes. Part 1 is completed and part 2 is ongoing after confirming canakinumab 300 mg Q3W as RP3R. Clinical trial identification: ACZ885V2301/NCT03626545. Legal entity responsible for the study: Novartis. Funding: Novartis. Disclosure: D. Lim: Advisory / Consultancy: MSD, Novartis, Astra-Zeneca, Boerhinger-Ingelheim; Honoraria (self): MSD, Novartis, Boehringer-Ingelheim. Y. Goto: Speaker Bureau / Expert testimony: AstraZeneca, Eli Lilly, Chugai, Taiho Pharmaceutical, Boehringer Ingelheim, Ono Pharmaceutical, Bristol-Myers Squibb, Pfizer, MSD, Shionogi Pharma, Novartis; Advisory / Consultancy: Eli Lilly, Chugai, Taiho Pharmaceutical, Boehringer Ingelheim, Pfizer, Novartis, AstraZeneca, Glaxo Smith Kline; Research grant / Funding (self): AbbVie, Eli Lilly, Taiho Pharmaceutical, Bristol-Myers Squibb, Ono Pharmaceutical, Daiichi Sankyo, Pfizer, Novartis, Kyorin. B.C. Cho: Honoraria (self): Novartis, Bayer, AstraZeneca, MOGAM Institute, Dong-A ST, Champions Oncology, Janssen, Yuhan, Ono, Dizal Pharma, MSD; Advisory / Consultancy: Novartis, AstraZeneca, Boehringer Ingelheim, Roche, BMS, Ono, Yuhan, Pfizer, Eli Lilly, Janssen, Takeda, MSD; Research grant / Funding (self): Novartis, Bayer, AstraZeneca, MOGAM Institute, Dong-A ST, Champions Oncology, Janssen, Yuhan, Ono, Dizal Pharma, MSD; Shareholder / Stockholder / Stock options: TheraCanVac Inc; Licensing / Royalties: Champions Oncology . H. Kaneda: Honoraria (self): Novartis; Advisory / Consultancy: Novartis. J-H. Kang: Honoraria (self): Roche, AZ, Merck ; Advisory / Consultancy: AZ, MSD, Takeda; Research grant / Funding (self): AZ, Yuhan, CKD, Astellas. S-W. Kim: Advisory / Consultancy: AstraZeneca; Research grant / Funding (self): AstraZeneca, Lilly, Boehringer Ingelheim. C-H. Chiu: Honoraria (self): AstraZeneca, Bristol-Myers Squibb, Merck Sharp & Dohme, Novartis, Ono Pharmaceutical, Pfizer, Roche . J.C-H. Yang: Honoraria (self): Novartis, personal fees from Boehringer Ingelheim, personal fees from Eli Lilly, personal fees from Roche/Genentech, personal fees from Chugai, personal fees from MSD, personal fees from Pfizer, personal fees from Novartis, personal fees from BMS, persona; Advisory / Consultancy: Novartis, personal fees from Boehringer Ingelheim, personal fees from Eli Lilly, personal fees from Bayer, personal fees from Roche/Genentech, , personal fees from Astellas, personal fees from MSD, personal fees from Merck Serono, personal fees from Pfizer. W-C. Su: Travel / Accommodation / Expenses: BI, BMS. K. Obyrne: Advisory / Consultancy: Boehringer Ingelheim, Merck Sharpe and Dohme, Eli Lilly, AstraZeneca, Roche, Pfizer, Bristol-Myers Squibb, and Novartis. V. Papadimitrakopoulou: Advisory / Consultancy: Nektar Therapeutics, AstraZeneca, Arrys Therapeutics, Merck, LOXO Oncology, Araxes Pharma, F Hoffman-La Roche, Janssen Research Foundation, Bristol-Myers Squibb, Clovis Oncology, Eli Lilly, Novartis, Takeda, AbbVie, TRM Oncology, Tesaro, Exelixis, Gritsto; Honoraria (self): F Hoffman-La Roche; Research grant / Funding (self): Eli Lilly, Novartis, Merck, AstraZeneca, F Hoffman-La Roche, Nektar Therapeutics, Janssen, Bristol-Myers Squibb, Checkmate, Incyte (to institution). M. Reck: Speaker Bureau / Expert testimony: AbbVie, Amgen, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Lilly, Merck, MSD, Novartis, Pfizer, Roche; Advisory / Consultancy: AbbVie, Amgen, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Lilly, Merck, MSD, Novartis, Pfizer, Roche; Honoraria (self): AbbVie, Amgen, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Lilly, Merck, MSD, Novartis, Pfizer, Roche; Officer / Board of Directors: IASLC BOD, Member of Scientific Committee. I. Malet: Shareholder / Stockholder / Stock options: Novartis; Full / Part-time employment: Novartis. B. Mookerjee: Full / Part-time employment: Novartis; Shareholder / Stockholder / Stock options: Novartis, Glaxo Smith Kine, Incyte, AstraZeneca. Z. Zewen: Full / Part-time employment: Novartis; Shareholder / Stockholder / Stock options: Novartis. L. Paz-Ares Rodriguez: Advisory / Consultancy: Roche, Lilly, Novartis, Pfizer, BMS, MSD, Takeda, AstraZeneca, Boehringer Ingelheim, Bayer, Janssen, Celgene; Honoraria (self): Roche, Lilly, Novartis, Pfizer, BMS, MSD, Amgen, Merck, Sanofi, Takeda, AstraZeneca, Boehringer Ingelheim, Bayer, Janssen, PharmaMar, Celgene.